FEATURES THE FORMATION OF FOREIGN PAID SERVICES (Journal of actual problems of jurisprudence, 2021)
The topicality of the topic of the study. Basically, many scientists believe that the service in reimburs- able obligations is immaterial and may represent an intangible result, which is expressed in the actions of the service provider and the contractor, as well as in the non-property effect of these actions. In ob- ligations on the provision of services, the result of the activities of the service provider does not have a tangible form, it is intangible. This difference is reflected in civil law. It should be recognized that some services are aimed at the intangible result, while others – at the tangible. It seems to us, however, that the legislator distinguishes materialized services, since they are objects of contractual obligations, and intangible services are objects of obligations to provide services. In other words, the service provider cannot attract a third party to carry out the actions (activities) specified in the contract, which the service provider must perform if the parties have not established this in the contract. This rule applies to all con- tracts under the terms of which paid services are provided.Method of research. The methodological basis of scientific research is a set of methods of scientificknowledge, among which the leading place is occupied by the dialectical method. This scientific article uses General scientific methods of cognition, which, first of all, should include formal logical methods (analysis, synthesis, induction, deduction, analogy), as well as special legal methods (formal legal, the method of comparative law and system analysis).